Impact of resistance exercise order on postexercise hemodynamic measures in middle-aged and older women - Ágatha Graça; Daniel Vicentini de Oliveira; Alex Silva Ribeiro; Wendell Arthur Lopes; Rodrigo Garcia Fiorillo; Higor Santos Fonseca; Jerry L. Mayhew; Matheus Amarante do Nascimento (Motriz: Revista de Educacao Fisica, 2022)
Abstract Aim: to compare the impact of different resistance exercise orders on postexercise hemodynamic measures in resistance-trained nonhypertensive middle-aged and older women. Methods: Twenty-three women (age 50-78 yrs) were randomized into two resistance training (RT) groups: one group started training sessions performing multi-joint exercises followed by single-joint exercises (MS, n = 12; 58.92 ± 5.53 yrs), while the other group performed their sessions in the opposite order (SM, n = 11; 57.93 ± 11.89 yrs). Both groups performed their RT sessions composed of 7 exercises performed in 3 sets of 10-15 repetitions maximum. Blood pressure was measured by automated equipment during pre-training and at 10, 20, 30, 40, 50, and 60 min after the training session. Results: Repeated-measures analysis of variance (ANOVA) identified an isolated effect of time only for systolic blood pressure (p = 0.003) with statistically significant reductions in pre-session measurement at 60 min post-session in both groups (MS: 117.67 ± 15.89 mmHg vs. 111.25 ± 11.84 mmHg and SM: 118.64 ± 15.13 mmHg vs. 111.50 ± 15.62 mmHg). Regarding diastolic blood pressure and subjective perception of effort, no difference was identified between groups (p > 0.05). Conclusion: We conclude that a RT session can promote post-exercise hypotension for systolic blood pressure after 60 min of recovery in middle-aged and nonhypertensive older women regardless of the exercise order.